A new species of Hyla (Anura: Hylidae) from Cerro Las Flores, Oaxaca, Mexico - Meik, Jesse M.; Canseco-Márquez, Luis; Smith, Eric N.; Campbell, Jonathan A. (Zootaxa, 2005)
Hyla ephemera, new species, is described from the cloud forests of Cerro Las Flores in south-central Oaxaca, Mexico. We tentatively place this species in the phenetic H. bistincta group. It is most similar to H. calthula in color pattern but differs in having a greater snout–vent length, a relatively shorter snout and tibia, a relatively wider head, and a larger tympanum. We also report an additional locality record for H. calthula, previously known only from the type locality.